30 years of second-generation antiseizure medications: impact and future perspectives. Issue 6 (June 2020) - Perucca, Emilio; Brodie, Martin J; Kwan, Patrick; Tomson, Torbjörn
Summary: Since 1989, 18 second-generation antiseizure medications have reached the market, resulting in a greatly increased range of treatment options for patients and prescribers. 30 years have passed and now is the time for an appraisal of the effect of these medications on clinical outcomes. Every antiseizure medication needs to be assessed individually, but overall second-generation drugs are less likely to cause pharmacokinetic interactions than their older counterparts. Some second-generation antiseizure medications have shown advantages in tolerability and safety, particularly in the treatment of older patients and women of childbearing potential. Disappointingly, however, none of these medications appear to be more efficacious than first-generation antiseizure medications, highlighting the need for novel strategies in epilepsy drug development. Although second-generation antiseizure medications have not substantially reduced the proportion of patients with pharmacoresistant epilepsy, their availability has enabled more opportunities to tailor treatment choice to the characteristics of the individual.